MUATAN PROPAGANDA PADA MEDIA MASSA ( Analisis Isi Propaganda dalam Berita Perang Pada Majalah Djawa Baroe Masa Pendudukan Jepang Di Indonesia Tahun 1942-1945) - Kurniasih, Eti (Transformasi, 2017)
Djawa Baroe is a Japanese magazine in Indonesia during World War II in order to supportJapan during the war against allies. The magazine became the center of research object/interest,because it provides a large portion in preaching the Greater East Asia war. The purpose of thisstudy is to find out how the propaganda content in the Djawa Baroe Magazine in preaching awar event during the Japanese occupation in Indonesia from 1942 up to 1945 and to know thelevel of differences in the content of messages based on news topics, type of propaganda andpropaganda techniques.This research is an explanative research. It isdescribing facts and phenomena of a particularmessage or text, and also testing(how many)hypothesis. The technique of the data analysis iscontent analysis using chi square statistical test. It is applied to find out whether there issignificant difference in the message content. Based on the frequency of the contents of themagazine, the most emerging news topic is the spirit of nationalism and patriotism. It is clearlyseen that the Japanese Government efforts to provoke the Indonesian people to be willing tosacrifice, both materially and immaterial, to the struggle of the nation of Japan in liberatingAsia nations from the imperialists of Europe and America. The chi square test shows that in thenews topic category of type or type of propaganda, the value of X² is 20,809 with degrees offreedom (df)=4, then compared on the distribution table X² table=9.49. The value of X² exceedsthe critical value standards of 9,488. This means that there is a significant difference betweeneach type of propaganda on the news topic. In news topic category against propagandatechnique value X² is 50,251 with degree of freedom (df)=12, then compared on X² distributiontable. X²table value exceeds the critical value standard of 21.03. It can bae concluded there is asignificant difference of seven propaganda techniques on news topics in Djawa Baroe magazine.Keywords : Djawa Baroe, Content Analysis, Japanese Occupation, Propaganda Content